A Case Study of Multimodal Analysis: The Representation of a Female Model in the ‘Insight’ Rubric of Male Magazine 147th Edition - Vinakha Naraswas Sriratu (Passage, 2016)
The present study entitled “A Case Study of Multimodal Analysis: The Representation of a Female Model in the ‘Insight’ Rubric of Male Magazine 147th Edition” aims at discovering the image of Indonesian women presented in the men’s magazine visually and verbally. Using a descriptive qualitative method, this study applies multimodality based on Halliday’s (1994) Systemic Functional Linguistics to analyze the visual and verbal modes in the data. In the visual stage, the data are analyzed by Kress and van Leeuwen’s (2006) visual grammar, Wilfred’s (1962) meaning of colors, and Barnard’s (2007) theory of fashion and physical appearance. Meanwhile, the verbal data are analyzed Halliday’s (1994) transitivity. The findings show that the integrated visual and verbal modes complement each other to construct the image of the female model. The female model is visually represented as a physically and spiritually beautiful woman with aggressiveness. In addition, the female model is verbally represented as a hardworking, popular, and, curious woman who tends to use her feelings in life. Those representations can lead her to be the sex object for men yet powerful woman. In relation to the gender issue, the study concludes that the magazine reflects how women’s stereotypes change overtime depending on the cultural society.Keywords: Women’s representation, multimodality, visual analysis, verbal analysis, magazine